Socialization of Digital Marketing and Financial to UMKM Aliyah Textile - Desy Arigawati; Mariana Hakim Riandi; Yusi Risdaini; Ahmad Rofiq Amri; Elma Apriyani; Anisa Rahma Desi; Dina Novita; Erli Tyas Linggawati; Umiyati Snae; Rahmatullah, Rahmatullah; Arjun Ananda T; Yostra Herdiawan; Rizal Abdillah (Jurnal Pengabdian Masyarakat Formosa, 2024)
The rapid development of technology has had a major impact on human life, one of which is the aspect of business behavior of Micro, Small and Medium Enterprises. Micro, Small and Medium Enterprises (UMKM) entrepreneurship is expected to increase the creativity and ability of the community to channel their ideas and creations by utilizing available natural resources. Micro Small Medium Enterprises (UMKM) in Indonesia is one of the pillars of the Indonesian economy in addition to cooperatives. It is unfortunate if Aliyah Textile has not maximized online product sales, because it has not been able to reach global expansion marketing. So, we chose service at Aliyah Textile, with the aim of helping and unraveling the problems that exist at Aliyah Textile, and hope that Aliyah Textile can be more advanced and developed, because it has skills in digital marketing and finance. Socialization of digital marketing and finance to UMKM Aliyah Textile. Hopefully useful in long-term knowledge investment.